Influence of National Cultures on Operations Management and Supply Chain Management Practices—A Research Agenda - Gupta, Manjul; Gupta, Sushil (Production and Operations Management, 2019)
The role of national culture interactions is important in operations management and supply chain management decisions. Yet, cross‐cultural research in this field is limited. Our goal in this study is to review relevant research, to raise awareness about the critical role of national culture among operations management and supply chain management researchers, and to offer directions for future research. To achieve this goal, we report our research findings in three major categories: (i) Operational Decisions (innovation, and research and development, quality management, workforce management, performance measurement, and risk, security and disaster management); (ii) Supply Chain Management (buyer–supplier interactions, governance mechanisms, outsourcing, and offshore operations); and (iii) Interdisciplinary Topics (entrepreneurship, investments, joint ventures, and mergers and acquisitions). We also suggest methodological considerations for future research by those interested in studying national culture.